Design of a Microcontroller Based Wireless Measurement and Monitoring of Temperature and Relative Humidity using Zigbee - Nath, Sharmila; Baruah, Himadri (International Journal of Computer Sciences and Engineering, 2025)
This paper proposes an advanced remote monitoring system for the farmers to monitor the various environmental parameters required for the growth of crops. This method is cost effective and an improvisation of old techniques. It mainly measures the ambient temperature and relative humidity, using temperature and humidity sensor DHT11 and sends the data wirelessly to remote location using Zigbee based Wireless sensor network and is also displayed on LCD. An application is developed in LABVIEW to acquire the data corresponding to temperature and relative humidity graphically in real time.